Fertility outcomes in microdissection testicular sperm extraction for non-obstructive azoospermia - Mahour, Simmi; Nair, Sreelakshmy R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: The objective of this study was to evaluate outcome of micro dissection testicular sperm extraction (micro TESE) and intracytoplasmic sperm injection (ICSI) for treatment of non-obstructive azoospermia (NOA). Methods: We retrospectively analysed data of 96 consecutive patients with clinical NOA who were treated with micro TESE by single surgeon, between January 2022 and December 2022, in Lifeline superspeciality hospital Adoor, Kerela. Embryological and clinical outcomes were demonstrated based on ICSI-IVF cycles using fresh or frozen sperms, different etiologies of NOA and various counts of sperms retrieved. Results: 96 men underwent micro TESE and 72.9% (70/96) of them had sperms retrieved. ICSI performed in 64 couples. Of those, 41 reached the stage of embryo transfer (ET). Of the couples who underwent embryo transferred, 18 (43%) resulted in biochemical pregnancies and 7 (17%) clinical pregnancies. There was a significant difference in the testicular volume and serum FSH levels between micro-TESE positive and negative groups (p=0.000). Retrieval rates were higher in group of men with normal testicular volume and FSH<12. Clinical pregnancy rate was around 11% in couples who had sperms retrieved by micro TESE. The sperm retrieval rates were higher in men with age <40 years. Similarly younger the female age more was the pregnancy rate. Out of various etiologies idiopathic NOA and Klinefelter syndrome had better sperm retrieval rate in our study which was statistically significant. Total fertilization rate and blasts rates were 79.7% and 51.6% out of ICSI. Conclusions: Microdissection testicular sperm extraction is an effective treatment for NOA with higher rate of sperm retrieval and pregnancy rate. The increasing success rates over several years indicate the importance of surgical skill and laboratory staff experience.